1999
DOI: 10.1063/1.371425
|View full text |Cite
|
Sign up to set email alerts
|

Formation of SiC-surface layer by ion implantation

Abstract: A homogeneous SiC-surface layer is formed by implantation of 40 keV 13C carbon ions into single-crystalline silicon 〈100〉 with a fluence of 3.8×1017 ions/cm2 and subsequent electron beam rapid thermal annealing (EB-RTA). The carbon-depth distributions were analyzed with the resonant nuclear reaction 13C(p,γ)14N. In contrast to furnace annealing, EB-RTA (1150 °C for 15 min) leads to a carbon redistribution resulting in the formation of a homogeneous SiC-surface layer of about 50 nm in thickness. The carbon redi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…In this article we report on the formation of a thin a-Si 3 N 4 surface layer after implantation of 60 keV nitrogen ions into silicon, when the implanted sample was thermally treated under high vacuum conditions. This work continues a former investigation, which demonstrated that thin b-SiC surface layers on silicon are formed by carbon implantation into silicon and subsequent thermal treatment under high vacuum conditions [18][19][20]. This formation process is caused by the process of active oxidation of silicon.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…In this article we report on the formation of a thin a-Si 3 N 4 surface layer after implantation of 60 keV nitrogen ions into silicon, when the implanted sample was thermally treated under high vacuum conditions. This work continues a former investigation, which demonstrated that thin b-SiC surface layers on silicon are formed by carbon implantation into silicon and subsequent thermal treatment under high vacuum conditions [18][19][20]. This formation process is caused by the process of active oxidation of silicon.…”
Section: Introductionsupporting
confidence: 81%
“…The alteration of the 15 N depth profile during the thermal treating, from a Gaussianlike nitrogen depth distribution into a rectangular one, was also observed on carbonimplanted silicon samples being subsequently thermally treated just as under high vacuum conditions with scanned 20 keV electron beam [18][19][20]. It was demonstrated, that the carbon redistribution was not the result of a diffusion process, but of silicon etching as shown by an experiment with a depth marker [18].…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…At the O 2 pressure of 3 Â 10 -7 mbar and sample temperature above 750 C the interaction of O 2 with Si results in forming volatile SiO molecules at the surface [15,16]. Therefore, silicon not bonded with carbon is selectively etched leading to the formation of a SiC surface layer [10]. A further increase of annealing temperature does not alter this rectangular carbon depth distribution, which represents a SiC surface layer with a thickness of about 70 nm taking into account the bulk density of SiC.…”
Section: Resultsmentioning
confidence: 99%
“…However, observations of Reeson et al [8] on high temperature implantations suggest the presence of 6H-SiC structure in implanted silicon, but the existence of this phase was not proven. There are also indications for the presence of the 6H-SiC modification in the thin SiC surface layer produced by low energy carbon implantation into silicon and post annealing under high vacuum conditions [10]. The aim of this work is to characterize the structure of this SiC surface layer in detail using XRD and HRTEM.…”
Section: Introductionmentioning
confidence: 99%